2020
DOI: 10.1186/s40885-020-00138-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dietary adherence to the guidelines for prevention and treatment of hypertension among Korean adults with and without hypertension

Abstract: Background: Although dietary modification is strongly recommended for prevention and treatment of hypertension, little is known about which factors are associated with adherence to dietary guidelines. We investigated knowledge and attitude, perceived benefits of, barriers to, and self-efficacy of dietary therapy, and identified the factors associated with dietary adherence among adults with and without hypertension. Methods: We collected information on the knowledge/attitudes and perceived benefits of dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…This finding was higher than the study conducted in the southern part of Ethiopia, Korea, and Jordan where compliance with the recommended lifestyle was 27.3%, 35.5%, and 23%, respectively. 9,13,14 The higher level of adherence in this study compared with other studies in Ethiopia may be due to the higher health literacy level in Addis Ababa as patients are exposed to more information than in the rural part of Ethiopia. This report showed that a sedentary lifestyle was still high in developing countries like Ethiopia which increased the burden of chronic diseases like hypertension.…”
Section: Discussionmentioning
confidence: 55%
“…This finding was higher than the study conducted in the southern part of Ethiopia, Korea, and Jordan where compliance with the recommended lifestyle was 27.3%, 35.5%, and 23%, respectively. 9,13,14 The higher level of adherence in this study compared with other studies in Ethiopia may be due to the higher health literacy level in Addis Ababa as patients are exposed to more information than in the rural part of Ethiopia. This report showed that a sedentary lifestyle was still high in developing countries like Ethiopia which increased the burden of chronic diseases like hypertension.…”
Section: Discussionmentioning
confidence: 55%
“…Another study conducted in Thailand among hypertensive patients in Bangkok showed that although hypertensive patients were aware of their uncontrolled hypertension, they still chose to have a high salt diet due to a preference for tastier and instant food [48]. The pattern of the findings from other countries was similarly observed, such as in Ethiopia [49,50], Nepal [42], India [51,52], Australia [53], Iran [54,55], Spain [56], and Korea [57]. These studies revealed that individuals generally have a reasonable knowledge of the salt and its adverse effects of overconsumption as well as their favorable attitudes toward salt reduction; however, almost none of them took action to reduce salt intake, and their blood pressure was still uncontrolled.…”
Section: Discussionmentioning
confidence: 88%
“…For example, elderly patients with heart failure (HF) had decreased physical function due to decreased cardiorespiratory health and muscle strength, thereby reducing participation in physical activities [ 48 ]. On the other hand, compared with older adults without PDH, people with PDH were more likely to have lower self-efficacy [ 49 ], which reduced physical activities [ 50 ]. In addition, health intervention studies also supported our results, showing that the health conditions of hypertensive patients were also the main reason why these patients did not participate in physical activity programs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%